Bioengineering 3D Neural Networks Using Magnetic Manipulations (Adv. Funct. Mater. 50/2022). (9th December 2022) - Plen, Reut; Smith, Alejandra; Blum, Ofir; Aloni, Or; Locker, Uri; Shapira, Zehavit; Margel, Shlomo; Shefi, Orit
Abstract : Neural Engineering In article number 2204925, Orit Shefi and co‐workers depict that neurons are transformed into magnetic units and dynamically localized within 3D biomaterials using magnetic manipulations. Iron‐oxide nanoparticles are synthesized and incorporated into neurons, which are then subjected to various magnetic fields. The neurons' movement is controlled inside multi‐layered 3D collagen scaffolds simulating in‐vivo tissue structures, thus constructing pre‐designed, viable and functional 3D microarchitectures of neural networks.